Tuesday

July 22, 2014

July 22, 2014

Posted by **Lucy** on Saturday, August 30, 2008 at 8:40pm.

tanx/cotx - secx/cosx = 2/cscx

a) cscx=1

b) sinx=-1/2

c)cscx=-1

d)sinx=1/2

- Pre-Calculus -
**Reiny**, Saturday, August 30, 2008 at 11:08pm(sinx/cosx)/(cosx/sinx) - (1/cosx)/cosx = 2sinx

(sin^2 x)/(cos^2 x) - 1/cos^2 x = 2sinx

(sin^2 x - 1)/cos^2 x = 2sinx

(sin^2 x - 1)/(1 - sin^2 x) = 2sinx

-1 = 2sinx

sinx = -1/2

**Related Questions**

drwls - My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an ...

trig - express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is ...

Math - Im really struggling with these proving identities problems can somebody ...

calculus - express in sinx 1 1 ---------- + -------- cscx + cotx cscx - cotx and...

Math - Im really struggling with these proving identities problems can somebody ...

Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...

Pre Calculus - (secx)/(tanx)+(cscx)/(cotx)=secx+cscx Please help me verify this ...

Math - I'm only aloud to manipulate one side of the problem and the end result ...

Pre-Cal - How do I do these questions? I'm supposed to prove them so that both ...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...